Are there prospects for future economic integration among Muslim countries? Evidence from selected OIC countries - Mohd Amin, Ruzita; Hamid, Zarinah; Md Saad, Norma (Faculty of Economics and Management, Universiti Putra Malaysia, 2011)
Since mid-1980s, trade has been one of the main agenda among the Organization of Islamic Conference (OIC) member countries as a means towards achieving higher economic development. January 1st, 2009 has been declared as the target date for the establishment of the Trade Preferential System among the OIC countries, by which date intra-trade should be increased to 20%. Malaysia, which is considered to be one of the more successful economies among the OIC countries, is expected to play a pivotal role in enhancing intra-trade and ensuring that the targets are achieved. This paper investigates the degree of intra-trade activities among six OIC members, namely Egypt, Jordan, Malaysia, Saudi Arabia, Syria and Oman. It analyzes the trade structure of these OIC members utilizing “revealed comparative advantage” indices, “trade concentration”, and “trade competition” profiles. The findings show only small potentials for higher intra-OIC trade, generally in chemicals and materials, food and live animals, manufactured goods, and machinery and transport equipment. This indicates that much greater efforts need to be undertaken by OIC countries to prepare themselves for the establishment of an Islamic Common Market.